Simulação CFD de um leito de jorro cônico utilizando OpenFOAM - Baudel, Paulo Henrique de Sousa (Universidade Federal de São Carlos, 2021)
The performance of open-source computational fluid dynamics (CFD) software, OpenFOAM, relative to the widely-used Ansys suite of CFD software, was evaluated through the validation of two equivalent simulations of a spouted bed utilizing the two-fluid model (TFM). The grid used in the simulation was created in Meshing, part of the Ansys suite, and imported to OpenFOAM through an internal command, then validated by grid independence tests through the calculation of a Grid Convergence Index (GCI). Experimental tests were run according to the methodology proposed by Mathur and Epstein (1974), aiming to obtain the equipment's characteristic curve and determine operational fluid dynamic parameters. OpenFOAM performed in a satisfactory manner, resulting in shorter simulation times and greater precision in obtaining characteristic parameters such as stable spout height and minimum spout velocity; however, local grid collapses due to faulty mesh conversion were noted, which led to distortion in the spout regimes and impacted on the visualization of the simulation behaviour as seen in the volumetric solid fraction contour plots. The two-fluid approach was shown to be adequate for both softwares, despite the differences noted between experiment and simulation shown for the pressure drop versus velocity curve. It was concluded that, despite the heavy influence of local cell collapses suffered in the mesh conversion, OpenFOAM is entirely capable of generating good results for spouted bed simulations, with the added benefits of free and open-source use and enhanced processing speed, even in cases where the mesh used is highly complex relative to what is usually employed in similar works.
CFD simulation of spouted bed using OpenFOAM
Keywords: CFD; Código aberto; OpenFOAM; Leito de Jorro; TFM; GCI; Ansys Fluent; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA